Design and Development of Gastroretentive Tablets of Coccinia grandis leaf extract for treating Helicobacter pylori infection (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: To design and develop a gastroretentive herbal formulation of Coccinia grandis for the treatment ofHelicobacter pylori infection. Material and Methods: C. grandis extract was obtained by soxhlation processwith ethanol as the menstrum. The herbal gastroretentive tablets containing 200 mg of C. grandis ethanolicextract were prepared by direct compression method using effervescent technique. HPMC K4M, HPMC K100M,Carbopol and guar gum were used as retarding polymers at various concentrations. Sodium bicarbonate was usedat 20%w/w as gas generating agent and Avicel at 35%w/w as diluent. FTIR and DSC methods were employedto investigate the drug-excipient interactions. The formulated tablets were evaluated for various quality controlparameters. Results and Discussion: The FTIR and DSC study revealed that there was no interaction betweenthe extract and the excipients. All the formulated tablets were within the quality control limits. The kinetic studiesspecified that the release of extract from the gastroretentive tablets was by erosion-controlled diffusion mechanism.Conclusion: The formulation having the combination of gum with HPMC K15M exhibited minimum floating lagtime and good release pattern which followed first-order kinetics.